Inadequate postpartum screening for type 2 diabetes in women with previous gestation diabetes mellitus: A retrospective audit of practice over 17 years. Issue 9 (14th July 2021) - Ward, Rebecca J.; Fryer, Anthony A.; Hanna, Fahmy W.; Spencer, Nathaniel; Mahmood, Madia; Wu, Pensee; Heald, Adrian H.; Duff, Christopher J.
Abstract: Introduction: Women with gestational diabetes (GDM) are at greatly increased risk of type 2 diabetes (T2DM). The UK guidance recommends screening for T2DM at around 6‐week postpartum and annually thereafter. We evaluated conformity to this guidance in two separate time periods. Methods: The proportion of tests performed within guidance was assessed using longitudinal plasma glucose and glycated haemoglobin data in two cohorts (1999‐2007, n = 251; 2015‐2016, n = 260) from hospital records on women previously diagnosed with GDM. Results: In the 1999‐2007 and 2015‐2016 cohorts, 59.8% and 35.0% of women had the recommended postpartum testing, respectively ( P  < .001); just 13.5% and 14.2%, respectively, underwent the first annual test on time. During long‐term follow‐up of the 1999‐2007 cohort (median follow‐up: 12.3 years), the proportion of women tested in any given year averaged 34.2% over a 17‐year period; there was a progressive decline in the proportion of women receiving a yearly test with time since delivery ( P  = .002). Over the follow‐up period, 85 women from the 1999‐2007 cohort developed blood test results in the diabetic range with a median time to presumed DM diagnosis of 5.2 years (range 0.11‐15.95 years). Kaplan‐Meier analysis showed that 18.8% of women had blood test results in the diabetes range by 5‐year postpartum and 37.8% by 10‐year postpartum. Conclusions: Despite high profile guidelines and a clear clinical rationale to screen women with a past diagnosis of GDM, many women did not receive adequate screening for T2DM both in the short term and long term. This suggests that alternative approaches are needed to ensure effective follow‐up of this high‐risk group. To have an impact, interventions need to be tailored to a young, generally healthy group in which traditional approaches to follow‐up may not be best suited.